Colonization and Establishment of Exallomochlus hispidus (Morrison) (Hemiptera: Pseudococcidae) From the Field Colony to Laboratory Colony. Issue 1 (1st April 2022) - Indarwatmi, M
Abstract: The mealybug Exallomochlus hispidus is a polyphagous pest, some of its hosts are important fruits. This pest control research requires laboratory colonies in large numbers. The purpose of the research was to study the colonization and establishment of E. hispidus from the field colony into laboratory colony. E. hispidus was collected from infected mangosteen fruit. Kabocha was put in a plastic container containing mealybugs in the mangosteen fruit. Observations on the number of mealybugs that moved from mangosteen to kabocha were carried out every 24 hours for 72 hours. Establishment parameters observed were life cycle, adult longevity, and reproduction for three generations. The results showed that on the 24 hours, more mealybugs moved than on the 48 and 72 hours. In the 2nd generation of the laboratory colony, it shows that the life cycle was shorter, the adult longevity was longer and the reproduction was higher than field and 1st generation. The success of laboratory colonization and establishment will support the success of the experiments.